ANALISIS TINGKAT KEPUASAN KARYAWAN TERHADAP KOMPENSASI FINANSIAL DAN NON FINANSIAL YANG DIBERIKAN PERUSAHAAN (Studi Kasus di PT. Arjuna Yoga Sakti Bali) - Dwiningrum, Novi; Ganda Putra, Gusti Putu; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember)
The aims of this research were (1) to analyze the level of employee satisfaction, (2) to determine the effect of compensation variabels that given by the company against to the level of employee satisfaction, and (3) to determine the position of each compensation variabel against to the level of employee satisfaction at PT. Arjuna Yoga Sakti. Method of this research was surveying method. Data of this research were collected by spreading the questioner to 20 respondents. Then the data was processed using validity test, reability test, index of satisfaction test, and importance performance analysis. Result showed that employee feel quite satisfied based on the level of employee satisfaction was 58,22% of compensation variabel company. The formation counseling division has the high adjustability level and the remuneration variabel has the low adjustability level. The priority variabel that has to fixed was all the variabel that contained in quadrant A were: comfortable working area, remuneration, working uniform, and amount of bonus and commissions.
Keywords: 75,